2020
DOI: 10.1016/j.injury.2020.02.110
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation and selection of lower limb lymphedema patients for lymphaticovenular anastomosis: A prospective study

Abstract: Background: Lymphaticovenular anastomosis (LVA) with supramicrosurgical technique has recently gained popularity as a treatment method for patients with lymphedema. The aim of this study was to prospectively evaluate objective changes in leg volume in patients operated with LVA for lymphedema in the lower extremity, and to find positive predictors for the treatment method to facilitate the location of the venules and lymphatic vessels. Patients & Methods: 31 consecutive patients with lymphedema in the lower ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 28 publications
0
6
0
Order By: Relevance
“…Lymphaticovenous anastomosis (LVA) has been the most frequently used operation technique to alleviate lymphedema by directly delivering lymphatic fluid into the venous system. [4][5][6] This promising microsurgical method requires precise anatomic information of lymph vessels for excision of nonfunctioning lymphatic segment and reconstruction of lymphatic drainage. 7 Lymphoscintigraphy is widely used as the main investigatory tool to confirm the lymphedema diagnosis, visualizing the functional status of the lymphatic system.…”
mentioning
confidence: 99%
“…Lymphaticovenous anastomosis (LVA) has been the most frequently used operation technique to alleviate lymphedema by directly delivering lymphatic fluid into the venous system. [4][5][6] This promising microsurgical method requires precise anatomic information of lymph vessels for excision of nonfunctioning lymphatic segment and reconstruction of lymphatic drainage. 7 Lymphoscintigraphy is widely used as the main investigatory tool to confirm the lymphedema diagnosis, visualizing the functional status of the lymphatic system.…”
mentioning
confidence: 99%
“…Overall, surgical complications were rare, and included a postoperative pelvic recurrence of lymphedema (one of 10 patients), 29 postoperative infection (two of 12 patients), 30 subcutaneous ecchymoses (six total patients across all studies), 32 , 71 , 78 cellulitis (a finding that is frequently seen in lymphedema patients before and after surgery), 67 lymphangitis (one of 26 patients), 84 and failed anastomoses (nine individual failed anastomoses in 48 patients and 80 total anastomoses). 75 While cellulitis appears to be the most common complication of LVA, followed distantly by postoperative ecchymosis, there were no reports whatsoever of any major complications such as donor site lymphedema, emergent need to return patients to the operating room, need for surgical revision, or patient death.…”
Section: Resultsmentioning
confidence: 99%
“…Studies were conducted retrospectively, other than 14 performed prospectively. 22,[28][29][30][31]42,47,52,[54][55][56]59,66,84 No randomized control trials (RCTs) were identified. Mean duration of lymphedema symptoms before treatment ranged from 12 months 29,65 to 11.4 years.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations